2009
DOI: 10.3109/00365520903367262
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial infusion chemotherapy using high-dose 5-fluorouracil and cisplatin with or without interferon-α for the treatment of advanced hepatocellular carcinoma with portal vein tumor thrombosis

Abstract: HAIC using high-dose 5-FU plus cisplatin achieved a good tumor response. Adding IFN-alpha did not show any additional beneficial effects in terms of tumor response rate or survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Hepatic arterial infusion of cisplatin and 5-FU using a subcutaneous infusion port has been widely used in Japan to treat advanced HCC because of its relatively high response rate (27.8–57.1%) (Ando et al , 2002; Eun et al , 2009; Ueshima et al , 2010; Kim do et al , 2011; Kim et al , 2011); however, no randomized control trial has been conducted to demonstrate its effectiveness and survival benefit. Most reports of HAIC were retrospective studies with small numbers of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic arterial infusion of cisplatin and 5-FU using a subcutaneous infusion port has been widely used in Japan to treat advanced HCC because of its relatively high response rate (27.8–57.1%) (Ando et al , 2002; Eun et al , 2009; Ueshima et al , 2010; Kim do et al , 2011; Kim et al , 2011); however, no randomized control trial has been conducted to demonstrate its effectiveness and survival benefit. Most reports of HAIC were retrospective studies with small numbers of patients.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, IFN induces p53, which enhances apoptosis by FU, and influences the cell cycle via p27 Kip1 or apoptosis via Bcl-xL [22,23]. From a clinical perspective, Takaki-Hamade et al [24] and Eun et al [25] concluded that combined IFN treatment did not have an incremental effect. Thus, the benefit of adding IFN to HAIC with FU has not been proven clinically.…”
Section: Discussionmentioning
confidence: 99%
“…cisplatin, 5-fluorouracil , epirubicin, mitomycin-C and interferon) are administrated individually or in combination for advanced HCC. Especially, administration of 5-FU with cisplatin (FP) has been commonly used for advanced HCC [9][10][11][12][13][14][15][16][17] because of their synergistic effects. 11,18,19 However, there is no consensus regarding the most useful method to administrate FP by HAIC.…”
Section: Introductionmentioning
confidence: 99%